2013
DOI: 10.1039/c3sc50653c
|View full text |Cite
|
Sign up to set email alerts
|

Withanolide A: synthesis and structural requirements for neurite outgrowth

Abstract: The exploration of different routes leading to the stereoselective synthesis of the neuritogenic steroid withanolide A is reported in full detail. Notable features of the synthesis include a Corey-Seebach homologation, a vinylogous aldol reaction, a singlet oxygen Schenck-ene reaction, and finally, a latestage Wharton transposition. Semi-synthetic elaboration of the natural product resulted in 15 derivatives allowing a better understanding of its inherent reactivity pattern as well as its biological properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 59 publications
(20 reference statements)
0
27
0
Order By: Relevance
“…However, among all WA is the major active constituent, which draws the attention of several pharmacologists in recent years for its utility in neuropharmacological therapy (Ahmad et al, ; Baitharu et al, ). The potential of WA and its analogs toward neuronal differentiation and neurotic outgrowth is also confirmed by Liffert et al (Liffert et al, ). Furthermore, the involvement of WA to convalesce synaptic loss and neuritic damage has also been well demarcated by both in vitro and in vivo models (Kuboyama, Tohda, & Komatsu, ).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, among all WA is the major active constituent, which draws the attention of several pharmacologists in recent years for its utility in neuropharmacological therapy (Ahmad et al, ; Baitharu et al, ). The potential of WA and its analogs toward neuronal differentiation and neurotic outgrowth is also confirmed by Liffert et al (Liffert et al, ). Furthermore, the involvement of WA to convalesce synaptic loss and neuritic damage has also been well demarcated by both in vitro and in vivo models (Kuboyama, Tohda, & Komatsu, ).…”
Section: Introductionmentioning
confidence: 64%
“…The potential of WA and its analogs toward neuronal differentiation and neurotic outgrowth is also confirmed by Liffert et al (Liffert et al, 2013). Furthermore, the involvement of WA to convalesce synaptic loss and neuritic damage has also been well demarcated by both in vitro and in vivo models (Kuboyama, Tohda, & Komatsu, 2005).…”
mentioning
confidence: 83%
“…Withanolide A possesses a reactive enone moiety in the A ring, an epoxy alcohol in the B ring, as well as a tetrasubstituted unsaturated lactone side chain. The main synthetic challenges arise from the stereoselective construction of the side chain, the oxidation pattern of the A and B ring, and the diastereoselective instalment of a tertiary alcohol at C20 (35). Furthermore, structure-activity relationship studies have confirmed that the unsaturated ring A and epoxide play an important role in the cytotoxic activity of withanolides (32).…”
Section: Discussionmentioning
confidence: 95%
“…[196] The Gademann research group designed a synthesis of (+)- 218 starting from pregnenolone ( 224 ; Scheme 36). [197] Crucial steps of this approach include: a) a vinylogous aldol reaction between aldehyde 225 and the lithium enolate of 226 to afford lactone 227 ; and b) an elegant singlet oxygenene reaction [198] to produce the C5 tertiary alcohol of 228 . The singlet oxygen was generated in situ from oxygen under irradiation with a Na lamp in the presence of mesotetraphenylporphyrin (TPP) as the sensitizer.…”
Section: Neurotrophic Natural Productsmentioning
confidence: 99%
“…[196b] However, conflicting results precluded a clearer view of the mechanism of action of 218 . [197a,199] …”
Section: Neurotrophic Natural Productsmentioning
confidence: 99%